KELAS REPERTOAR PADA PEMBELAJARAN GITAR - Wicaksono, Herwin Yogo (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
Repertoire classes have not become a common practice in many informal institutions conducting guitar learning even though some formal institutions have done the practice. To implement repertoire classes needs appropriate time and places. Repertoire classes regularly conducted are proven to improve students' motivation to learn, decrease their nervousness and increase their selfconfidence. Besides, such classes motivate them to compete in improving their skill and become places to socialize among them. Key words: repertoire, guitar learning and students' self confidence